507 Seizure Control in Glioma Related Epilepsy: Proposal of a Qualitative Attribute Selection for a Discrete Choice Experiment into Patient Priorities for Treatment Goals. (19th August 2022) - Clynch, A; Elliott, M; Holmes, E; Marson, T; Jenkinson, MD
Abstract: Introduction: Seizures occur in ∼50% of high-grade glioma and >80% of low-grade glioma patients. Recurrent seizures affect >50% of low-grade gliomas. Both seizures and anti-epileptic drugs (AEDs) can impact health-related quality of life (HrQOL). Little is known about the patient preferences that feed into prescribing decisions in glioma-related seizures. Aim: To explore key outcomes patients value in the treatment of glioma related epilepsy. To select attributes for a future Discrete Choice Experiment (DCE) that analyses the attributes traded by patients in decision making. Method: Attribute lists will be formulated in 3 stages: (1) systematic review of glioma and epilepsy literature; (2) clinician review to highlight missing outcomes and (3) patient focus groups. There will be ∼6 focus groups on total: 4 initial concept development focus groups and 2 detailed focus groups analysing the phrasing of attributes. Patients' recruitment starts in November 2021. Results: Focus group transcripts will be analysed using qualitative analysis methods of thematic analysis and case deviant analysis to identify common themes and how they relate to population variables. If thematic analysis suggests a high level of heterogeneity between group sessions additional focus groups may be required. A ranked list of variables will be generated based on factors including tumour grade, primary vs recurrent tumour, seizure type and time since diagnosis. Conclusion: There is limited research examining outcomes patients value throughout their own treatment. This study will allow clinicians to gain a much-needed insight into patient priorities during the management of glioma-related seizures.